KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH SEBAGAI DETERMINAN MOTIVASI KERJA GURU: STUDI KASUS DI SD NEGERI RAWA KABUPATEN TASIKMALAYA - Waska Warta; Aprilia Nazyaati Nadiah; Surya Hari Mulyana; Sri Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and describe the role of principal's transformational leadership as a determinant of teacher work motivation at SD Negeri Rawa, Sukahening District, Tasikmalaya Regency. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interview techniques with primary informants (the principal), key informants (senior and junior teachers), and supporting informants (the school committee), reinforced by passive participatory observation and documentation studies. Data analysis techniques utilized the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The trustworthiness of the data was tested through source triangulation, technical triangulation, and member checks. The results indicated that the principal has optimally and consistently implemented four dimensions of transformational leadership (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration). This implementation serves as a strong determinant in boosting both intrinsic and extrinsic motivation of teachers. The implications are reflected in the increase in teachers' independent discipline, the emergence of a collaborative spirit through the weekly